2017
DOI: 10.1142/s0217732317502224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fierz transformation on gap equation and CEP at finite chemical potential and finite temperature in Hartree–Fock approximation

Abstract: Three representations of Nambu–Jona-Lasinio interaction Lagrangians are constructed by Fierz transformation, and gap equation and critical end point in these three representations at finite temperature and finite chemical potential are studied. We find that the values of the quark mass and the critical end point are different in these three representations because of the consideration of Hartree–Fock approximation in our calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…First, the curves of chiral susceptibility show that the chiral transition takes the form of a crossover. Although in some studies [15,32,33] the transition is a first order phase transition, it is found that when the vector interaction is strong enough, the first order phase transition turns to the crossover [15,21]. Second, the position of peak shifts toward smaller chemical potential as the parameter α decreases.…”
Section: Thermodynamic Propertiesmentioning
confidence: 96%
“…First, the curves of chiral susceptibility show that the chiral transition takes the form of a crossover. Although in some studies [15,32,33] the transition is a first order phase transition, it is found that when the vector interaction is strong enough, the first order phase transition turns to the crossover [15,21]. Second, the position of peak shifts toward smaller chemical potential as the parameter α decreases.…”
Section: Thermodynamic Propertiesmentioning
confidence: 96%